Новый вид гименолепидид травника - Wardium smogorjevskajae sp. n. (Cestoda, Cyclophyllidea) - Корнюшин, В.В.; Спасский, А.А. (Вестник зоологии, 1967)
When studying cestodes of snipes on the Black Sea Coast, sixty individuals of Tringa totanus L. nesting on the Tendrovsky Bay Coast were dissected for the complete helminthological investigation. They appeared to be infested to a great extent by cyclophyllidian cestodes of the genus Wardium namely, of representatives of new species Wardium named after the Ukrainian parasitologist L. A. Smogorzhevskaya. A description, drawings, and differential diagnosis of the new species are given. The basic characters of a new species are: the scolex has 10 aploparksoid hooks 0.034-0.037 mm long, three testicles are in a line, the uterus is sacklike. The type is kept in the Institute of Zoology, Academy of Sciences, Ukrainian SSR.